2021
DOI: 10.1002/pat.5265
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of silk plain‐weft knitted scaffolds for bladder tissue engineering applications

Abstract: Appropriate mechanical properties in both longitudinal and circumferential directions are an important requirement for the scaffold aimed at tissue engineering of the human urinary bladder. In this research, three weft-knitted silk fibroin scaffolds with stitch densities of 138, 182, and 245 loops/cm 2 were fabricated and studied for potential use in bladder regeneration applications. It was shown that the porosity and surface porosity of the scaffolds increased as stitch density decreased. Moreover, increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Biomechanically, polyglactin mesh was also superior to the other biomaterials in both strain and stress tolerance, and was the closest overall mimic of native porcine tissues. Knitted constructs are known as proper scaffolds for regeneration of load-baring tissues [ 27 , 28 ], and within this field of mechanobiology, it has been shown that stiffness of a biomaterial is known to give cellular state feedback, which can determine the fate of mesenchymal cell differentiation and is required to produce gene expression signatures that mimic the target tissues [ 29 , 30 ]. However, the force exerted on an organ and the required physiological functions can vary over time.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanically, polyglactin mesh was also superior to the other biomaterials in both strain and stress tolerance, and was the closest overall mimic of native porcine tissues. Knitted constructs are known as proper scaffolds for regeneration of load-baring tissues [ 27 , 28 ], and within this field of mechanobiology, it has been shown that stiffness of a biomaterial is known to give cellular state feedback, which can determine the fate of mesenchymal cell differentiation and is required to produce gene expression signatures that mimic the target tissues [ 29 , 30 ]. However, the force exerted on an organ and the required physiological functions can vary over time.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, silk is a natural protein fiber, and its superior mechanical properties, biocompatibility, as well as degradability make it very suitable for bladder reconstruction (Bhattacharjee et al, 2017;Nguyen et al, 2019;Li and Sun, 2022). Tavanai and others produced weft-knitted silk fibroin (SF) scaffolds (138, 182, and 245 loops/cm 2 of stitch density respectively), and evaluated their suitability for bladder regeneration (Figure 3) (Khademolqorani et al, 2021). Weft-knitted scaffolds have the following structure characteristics: perpendicular connecting wale and course loops (Eltahan et al, 2016;Cai et al, 2020;Meng et al, 2020).…”
Section: Natural and Synthetic Materialsmentioning
confidence: 99%
“…Among them, silk is a natural protein fiber, and its superior mechanical properties, biocompatibility, as well as degradability make it very suitable for bladder reconstruction ( Bhattacharjee et al, 2017 ; Nguyen et al, 2019 ; Li and Sun, 2022 ). Tavanai and others produced weft-knitted silk fibroin (SF) scaffolds (138, 182, and 245 loops/cm 2 of stitch density respectively), and evaluated their suitability for bladder regeneration ( Figure 3 ) ( Khademolqorani et al, 2021 ). Weft-knitted scaffolds have the following structure characteristics: perpendicular connecting wale and course loops ( Eltahan et al, 2016 ; Cai et al, 2020 ; Meng et al, 2020 ).…”
Section: Biomaterialsmentioning
confidence: 99%